A hydropower scheduling model to analyze the impacts from integrated wind and solar powers. (September 2021) - Xie, Mengfei; Cheng, Xianliang; Cai, Huaxiang; Wang, Jinwen; Liu, Shuangquan; Chen, Qinggui; Liu, Xiangrui
Abstract: For deterministic hydropower scheduling problems, the modeling plays a more crucial role than algorithms or methods in handling real-world industrial challenges that shift engineers face. This paper presents a hydropower scheduling model that prioritizes multiple objectives and takes into account constraints on the plant-based operating zones, day-ahead transactional energy, water level targets, as well as the wind and solar powers integrated so as to analyze their impacts on the hydropower scheduling. The model is applied to the Lancang River, which, with 11 cascaded reservoirs involved, presents a large-scale hydropower system. Typically, it takes about 4 s for the CPLEX 12.6 Solver to find the optimum for a quarter-hourly hydropower scheduling during a day. The case studies show that integrating the wind and solar powers into the power systems will make hydro-plants fluctuate in generation and put in generating capacity more in dry seasons than in wet seasons, causing loss of hydropower generating efficiency and increase of turbine maintenance pressure in dry seasons.